A high-density SNP-based linkage map of the chicken genome reveals sequence features correlated with recombination rate - Groenen, Martien A.M.; Wahlberg, Per; Foglio, Mario; Cheng, Hans H.; Megens, Hendrik-Jan; Crooijmans, Richard P.M.A.; Besnier, Francois; Lathrop, Mark; Muir, William M.; Wong, Gane Ka-Shu; Gut, Ivo; Andersson, Leif (Genome Research, 2009)
The resolution of the chicken consensus linkage map has been dramatically improved in this study by genotyping 12,945 single nucleotide polymorphisms (SNPs) on three existing mapping populations in chicken: the Wageningen (WU), East Lansing (EL), and Uppsala (UPP) mapping populations. As many as 8599 SNPs could be included, bringing the total number of markers in the current consensus linkage map to 9268. The total length of the sex average map is 3228 cM, considerably smaller than previous estimates using the WU and EL populations, reflecting the higher quality of the new map. The current map consists of 34 linkage groups and covers at least 29 of the 38 autosomes. Sex-specific analysis and comparisons of the maps based on the three individual populations showed prominent heterogeneity in recombination rates between populations, but no significant heterogeneity between sexes. The recombination rates in the F1 Red Jungle fowl/White Leghorn males and females were significantly lower compared with those in the WU broiler population, consistent with a higher recombination rate in purebred domestic animals under strong artificial selection. The recombination rate varied considerably among chromosomes as well as along individual chromosomes. An analysis of the sequence composition at recombination hot and cold spots revealed a strong positive correlation between GC-rich sequences and high recombination rates. The GC-rich cohesin binding sites in particular stood out from other GC-rich sequences with a 3.4-fold higher density at recombination hot spots versus cold spots, suggesting a functional relationship between recombination frequency and cohesin binding.
10.1101/gr.086538.108